Factors that predict urinary retention in patients who underwent inguinal hernia repair - Celasin, Haydar; Afandiyev, Faraj; Culcu, Serdar (International Surgery Journal, 2020)
Background: Some of the patients that undergo inguinal hernia repair develop urinary retention. We aimed to determine the rate of development of urinary retention and predicting factors after inguinal hernia repair. Methods: Patients who underwent inguinal hernia in our center from January 2017 to January 2020 were included in the study. Patients were examined in 2 groups; group1 (developed urinary retention after inguinal hernia repair) and group 2 (did not develop urinary retention after inguinal hernia repair). We investigated the relationship between the development of urinary retention with age, perioperative history of benign prostate obtruction, hernia type and localization, duration of surgery and anesthesia, perioperative non-steroidal anti-inflammatory drug (NSAID), narcotic analgesic and antispasmolytic use, having diabetus mellitus (DM) and rheumatoid diseases, and perioperative fluid replacement. Results: in group 1 and group 2, urinary retention developed in 11 (7.6%) of the patients. Patients who developed post-urinary retention were older than those without urinary retention (p=0.007). The BPO, DM rates were higher (p=0.0001), anesthesia and operation times were longer (p=0.003; p=0.0001); perioperative antispasmolytic use was higher (p=0.0001); we determined that postoperative fluid replacement rate was higher (p=0.003) and the rate of preoperative NSAID use was lower (p=0.0001). Clavien grade 4 and grade 5 complications were not observed in patients. Conclusions: Elderliness, DM history, antispasmolytic use, long operation and anesthesia duration, excessive postoperative fluid replacement and, not using perioperative NSAID increases the risk of urinary retention.